Who is Chloe Kim? - Loh, Stefanie; Gutierrez, Manuel (Illustrator), 1975- (New York : Penguin Workshop, 2022)
Learn about the life and career of Olympic gold medalist and legendary snowboarder Chloe Kim.
Includes bibliographical references (page 49).
6.7.
3-6.
Keywords: Kim, Chloe, -- 2000- -- Juvenile literature; Women snowboarders -- United States -- Biography -- Juvenile literature; Snowboarders -- United States -- Biography -- Juvenile literature; Olympic athletes -- United States -- Biography -- Juvenile literature; Kim, Chloe, -- 2000-; Women snowboarders; Snowboarders; Olympic athletes; Women -- Biography; Korean Americans -- Biography; Biographies